Comparative Analysis of Financial Performance of Bank BPD DIY And Bank Jateng For The 2019-2022 Period - Wende, Maria Emerlinda; Paramitalaksmi, Ratri (Global Financial Accounting Journal, 2023)
This research aims to determine the comparison of financial performance between BPD DIY and Bank Jateng (formerly: BPD Jateng) in the 2019-2022 period. Research Method – This study uses descriptive analysis, this study uses financial ratio analysis tools, normality test, independent Sample T-test if the data is normally distributed, and Mann Whitney test if the data is not normally distributed. Findings - The conclusion of the research and discussion above, it can be said that Bank BPD DIY and Bank Jateng show significantly different financial performance as shown by the CAR ratio, while the ratio of NIM, ROA, NPL, and BOPO has no significant difference in financial performance. Implication – This research is expected to be a reference for consideration to analyze the comparison of BPD DIY and Bank Jateng and other banks in the future.